Lefort, Abensour and the question: What is 'savage' democracy?. (September 2019) - Nelson, Bryan
One of the more perplexing terms to appear across Claude Lefort's later oeuvre, 'wild' or 'savage' democracy ( démocratie sauvage ) has proved a difficult and divisive facet of Lefort's political philosophy. Enigmatic, provocative, stubbornly undefined, while savage democracy is often simply ignored by many scholars of Lefort's work, others, such as Miguel Abensour, place it at the very centre of their interpretation of his thought. This essay confronts the question directly. What is savage democracy? What is it that Lefort invites us to think with this curious phrase? How does it relate to his larger theory of democracy as a symbolic mutation or form of society? And is Abensour, who provides the most exhaustive analysis of the concept, correct to identity savage democracy as the key to grasping democracy as a spontaneous and emancipatory political activity? Considering both its conceptual origins and historical associations, this article contends that beyond a mere descriptive qualifier, savage democracy may ultimately be understood as a philosophical vehicle through which we are compelled to conceive democracy according to its most creative and transformative dimensions and capacities.